The Use of Technology in the Logistics Industry to Promote E-Commerce Businesses in Thailand - Viriyayingyong, Kobboon; Pathravishkul, Banthita (Hatyai Academic Journal, 2025)
The logistics industry in Thailand is currently encountering challenges; for example, the need to improve infrastructure, enhance efficiency and reduce costs in transportation, and compete between businesses, including the rapid growth of e-commerce businesses. This article studies the use of technology in the logistics industry to support domestic e-commerce businesses. The study found that the adoption of technology in the logistics sector can upgrade Thailand’s e-commerce businesses. Implementing centralized data management platforms and standardized systems can resolve issues related to inconsistent data connectivity between systems and improve logistics management efficiency. Investments in intelligent transportation management technology and automated warehouses can reduce costs and accelerate the delivery of goods. To solve problems in adopting logistics technology, comprehensive and systematic measures are required, ranging from the development of data management platforms, the support of access to advanced technology, to the integration of technology into logistics processes. Additionally, support from the government in infrastructure development, personnel training, and budget allocation is a crucial factor in strengthening Thailand’s logistics industry. This article will benefit the development of Thailand's logistics industry by improving operational efficiency, reducing costs, and increasing delivery speed. It also guides the government to develop infrastructure and support access to advanced technology to enhance the competitiveness of e-commerce businesses in the market sustainably.